Studies on Transparency of Financial Statements, Management of Zakat and Attitudes of Amil and Efforts to Increase Muzakki's Trust - Kautsar Riza Salman; Mujahidin Mujahidin (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
This study aims to obtain empirical evidence regarding the effect of financial statement transparency, zakat management, and amil attitudes on the level of trust of muzakki. The population used in this study is the muzakki who pay zakat through an amil institution called the Yatim Mandiri Institution. The data analysis technique was used Partial Least Square with SmartPLS version 3. The results of this study found the effect of zakat management and amil attitudes on the level of trust of muzakki, while the transparency of financial statements was not empirically proven to affect the level of trust of muzakki. Trustworthy and professional management of zakat can increase effectiveness and efficiency as well as increase the benefits of zakat for the welfare of the community so that it has a significant impact on the level of trust of muzakki towards amil zakat institutions. The attitude of amil who is always responsive and serves the best and places a priority scale in the distribution of zakat funds has proven to have a significant impact in increasing muzakki's trust in the amil zakat institution.